The social capital of Pomeranian rural areas: on the measuring, balance and perspectives of development - Goszczyński, Wojciech; Knieć, Wojciech (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
Abstract: This article presents an examination of results of a study, together with the original methodology used, on the level and balance of social capital in the rural areas of Pomerania, and how this can be related to the development potential of local communities. The results of studies in nineteen rural communities in Pomerania clearly indicated that levels of capital for development were not the main reason for poor development, but rather the a negative balance between various individual elements that, together, comprise social capital. Local inhabitants who were surveyed associate their ability to act with the lack of informal relationships with Public Sector and not locally based Non Governmental Organisations.The tendency observed has been for widespread appearance of ineffective and socially poorly viable communities, which, when there are initiatives and the availability of external development funds have little chance to implement projects or achieve results. Further it is the balance of social resources and poor institutional development which limits the potential for external involvement in the investigated communities. This drastically reduces the institutional capacity of communities and decreases the density of networks and relationships that links the community with managing its own development. The study showed that rural inhabitants in Pomerania do bestow trust in local self government, however relatively few participate in its work.Various variables were tested and of these research revealed a strong correlation between economic situation and balance of social capital of the respondent these, however did not correspond with predictions formed on the basis of a strong local identity and the dynamics of the community as a whole.
Keywords: kapitał społeczny; rozwój lokalny; aktywizacja społeczności lokalnych; wieś pomorska